Experimental Study of Silent Sonar - MARSZAL, Jacek (Archives of Acoustics, 2014)
Stealth is a frequent requirement in military applications and involves the use of devices whose signals are difficult to intercept or identify by the enemy. The silent sonar concept was studied and developed at the Department of Marine Electronic Systems of the Gdansk University of Technology. The work included a detailed theoretical analysis, computer simulations and some experimental research. The results of the theoretical analysis and computer simulation suggested that target detection and positioning accuracy deteriorate as the speed of the target increases, a consequence of the Doppler effect. As a result, more research and measurements had to be conducted to verify the initial findings. To ensure that the results can be compared with those from the experimental silent sonar model, the target’s actual position and speed had to be precisely controlled. The article presents the measurement results of a silent sonar model looking at its detection, range resolution and problems of incorrect positioning of moving targets as a consequence of the Doppler effect. The results were compared with those from the theoretical studies and computer simulations.